Block characteristics of Dexmedetomidine as an adjuvant to local anaesthetic in Infraclavicular brachial plexus block using peripheral nerve stimulator and ultrasound - Shrestha, Ujma; Moktan, Sushila Lama; Shrestha, Sanjay (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Dexmedetomidine has been frequently used in regional anaesthesia to improve the quality of blocks. Addition of dexmedetomidine to local anaesthetics has been shown to hasten the onset of both sensory and motor blocks and also prolong the duration of analgesia. The objective of this prospective comparative study was to assess the change in characteristics of infraclavicular brachial plexus block after adding Inj. Dexmedetomidine to 2% Lignocaine with Adrenaline.Methods: Sixty-six patients, scheduled for upper limb surgeries under ultrasound guided infraclavicular brachial plexus block were randomly allocated to two groups. Group LS received Inj. Lignocaine 2% with Adrenaline, 7mg/kg diluted to 30 ml with saline and Group LD received Inj. Dexmedetomidine 0.75 mcg/kg in addition to Inj. Lignocaine 2% with Adrenaline, 7mg/kg again diluted to a total volume of 30 ml. The parameters studied were: onset of sensory and motor blocks and duration of analgesia.Results: Sixty patients completed the study. The demographic variables and motor block were similar between both groups. The mean time to onset of sensory block was significantly faster in Group LD compared to Group LS (9.80±4.85 min vs 12.30±3.97 min, p=0.033). The duration of analgesia was also found to be prolonged in Group LD compared to Group LS (286.73±55.38 min vs 226.53±41.19 min, p < 0.001).Conclusion: Addition of 0.75 mcg/kg of Dexmedetomidine to 2% Lignocaine with Adrenaline hastens the onset of sensory block and prolongs the duration of analgesia in ultrasound guided and peripheral nerve stimulator guided infraclavicular block.